PENGARUH KETELADANAN GURU AKIDAH AKHLAK TERHADAP PEMBENTUKAN KARAKTER SISWA - Mas Teguh Wibowo; Azizah Hanum OK (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
In the context of concerns about teacher behaviour that does not motivate students, such as shouting at students, frequent teacher tardiness, or coldness in interactions with students, this study focuses on the impact of teacher exemplary behaviour on student character building at Mts Swasta Darul Ulum Budi Agung Medan. This study used a quantitative method with a descriptive correlational approach, including Pearson product moment correlation analysis and simple linear regression test. The results confirmed that teachers' exemplary behaviour in the aspects of creed and morals has a significant influence on students' character development, with a strong correlation level. The simple linear regression test shows that the exemplary behaviour of teachers in this case makes a positive contribution of 37.81% to student character. The validity and reliability of the research instruments have been well tested. These findings, reinforced by data analysis using SPSS version 20 software, emphasise the important role of teacher exemplarity in shaping student character in this educational institution, and encourage efforts to improve teacher exemplarity as a positive step to effectively shape student character.